Co-expression of Interleukin-17A molecular adjuvant and prophylactic Helicobacter pylori genetic vaccine could cause sterile immunity in Treg suppressed mice. (February 2020) - Nemattalab, Mehran; Shenagari, Mohammad; Taheri, Mojtaba; Mahjoob, Mohammad; Nazari Chamaki, Foroogh; Mojtahedi, Ali; Hasan-alizadeh, Elham; Ashrafkhani, Babak; Mousavi Niri, Neda
Highlights: The development of H. pylori vaccine became a priority in the field of vaccinology. The research was aimed at determining the role of some cytokines in H. pylori vaccine development. Either oipA alone, or oipA co-expressed with cytokines, promotes protective immunity. The highest Th17 cytokines were produced in Treg suppressed IL-17A receiving group. Treg suppressed mice administered with IL-17A/oipA developed sterile immunity. Abstract: The increasing clinical significance of Helicobacter pylori (H. pylori) in human stomach cancer has led to global efforts to eradicate this pathogen. Recent studies have confirmed the importance of some cytokines such as Interleukin-18 (IL-18), Interleukin-8 (IL-8), Interleukin-17A (IL-17A) and Interleukin-22 (IL-22) in the pathogenesis of the so-called bacterium. This study was designed to compare the effects of Type 1T helper (Th1), Type 2T helper (Th2) cells, Regulatory T cells (Treg) and T helper 17 (Th17) modulatory effects on the efficacy of designed H. pylori vaccine by incorporating some molecular adjuvants in Treg competent and Treg suppressed groups. A bicistronic vector was used for simultaneous expression of codon-optimized Outer inflammatory protein a (OipA) gene and modified mice IL-18, IL-17A, IL-22 and Foxp3 (forkhead box P3) cytokines from four cassettes. Immunization of mice groups was performed using produced plasmids intradermally. Specific IgG1 and IgG2 and IgA antibody titers produced in mice were confirmed by enzyme-linked immunosorbent assay (ELISA) in sera and intestine obtained four weeks after the last immunization. After being stimulated with a mixture of both anti-CD28 mAb and H. pylori lysate, frequencies of single Interferon-Gamma (IFN-γ), single IL-17 and dual IFN-γ/IL-17-secreting T-cells were documented using dual-color FluoroSpot. The kinetics of Th1, Th2 and Th17 in the immunized animals was determined by relative quantification of IL-17A, IL-22, IFN-γ, IL-8, IL-2 and IL-4 specific mRNAs. Four weeks after bacterial challenge, quantitative colony count in the isolated and homogenized stomachs was utilized to assess the level of protective immunity among all groups. The results of immunologic assays showed that the highest cell-mediated immunity cytokines were produced in IL-17 receiving group in which the Treg responses were suppressed previously by the administration of the Foxp3 as an immunogen. In addition, potent clearance of Helicobacter pylori infection was seen in this group as well.